New flavanol O-glycosides in grape and wine. (15th November 2018) - Zerbib, Marie; Mazauric, Jean-Paul; Meudec, Emmanuelle; Le Guernevé, Christine; Lepak, Alexander; Nidetzky, Bernd; Cheynier, Véronique; Terrier, Nancy; Saucier, Cédric
Highlights: Monomeric and dimeric flavanol hexosides were detected in grapes and wines by LC–MS. Specific MS fragments were obtained for these hexosides by using MS 2 an MS 3 . The level of monomeric hexosides raised during grape development. (+)-Catechin 4′- O - β and 7- O - β hexosides were hemi-synthesized and used as standards. Abstract: The presence of monomeric and dimeric flavan-3-ol monohexosides was investigated in grapes and wines. Polyphenol extracts were prepared from grape seeds and skins (Syrah, Merlot, and Cabernet-Sauvignon) sampled at three different developmental stages. Different wines (Tannat, Alicante, Syrah, Merlot, and Grenache) were also studied. The different samples obtained were analyzed by UPLC-ESI-IT-MS. Specific molecular ions corresponding to flavan-3-ol hexosides were detected by using targeted molecular ions with specific m / z values: 451 for ( epi )catechin hexosides, and 739 for procyanidin dimer hexosides. 4′- O - β -glucosyl-(+)-catechin and 7- O - β -glucosyl-(+)-catechin were obtained by using a glucosyl transferase from apple, UGT71A15, and their structures determined by NMR. These glucosylated monomers and the dimers were identified in all analyzed grape seed and several skin extracts at the different stages and in wines made from different varieties.